Becoming and being goth: How goths remember the scene's transition from the eighties into the nineties. (1st October 2021) - Bamford, Trevor; Ibrahim, Joseph; Spracklen, Karl
Goth emerged from post-punk, and by the 1980s became an identifiable feature of the popular music scene and wider popular culture. Fuelled by the success of bands such as the Sisters of Mercy, goth music and culture spread around the world, interacting with wider alternative, gothic fashions. At the end of the 1980s, goth reached a peak of interest followed by retrenchment into the alternative, subcultural spaces from which it had emerged. Nonetheless, it survives. In this article, we interview goths who became active in the 1980s and who remain engaged in order to understand how they became goths and what goth meant to them then. Using memory work, we are interested in how these goths construct their own histories and mythologies, and what this might tell us about the political and sociological importance of goth as a counter-hegemonic space at a time of globalization, consumption and commodification. We explore how they remember goth emerging from the post-punk scene with its radical politics and alternative, anti-mainstream culture. We examine the way these individuals remember becoming goth and their awareness of being in a goth scene. We then show how they remember and construct stories of when goth retrenched in an alternative underground that reconstructed the counter-hegemonic politics of punk and post-punk. Finally, we show what happened in the late 1980s and early 1990s and argue that the scene, or that part of the scene represented by our goths, is following a dialectical path carved out of the neo-Gramscian concept of negotiation when faced with the culturally and aesthetically hegemonic effect of a dominant culture.